Effect of PF-00547659 on Central Nervous System Immune Surveillance and Circulating β7+ T Cells in Crohn's Disease: Report of the TOSCA Study. (16th September 2017) - D'Haens, Geert; Vermeire, Séverine; Vogelsang, Harald; Allez, Matthieu; Desreumaux, Pierre; Van Gossum, Andre; Sandborn, William J; Baumgart, Daniel C; Ransohoff, Richard M; Comer, Gail M; Ahmad, Alaa; Cataldi, Fabio; et al.
Abstract: Background and Aims: Progressive multifocal leukoencephalopathy [PML], a brain infection associated with anti-integrin drugs that inhibit lymphocyte translocation from bloodstream to tissue, can be fatal. Decreased central nervous system [CNS] immune surveillance leading to this infection has been reported in patients with multiple sclerosis or Crohn's disease treated with anti-integrin antibody natalizumab. PF-00547659 is an investigational human monoclonal antibody for inflammatory bowel disease, targeted against α4 β7 -mucosal addressin cell-adhesion molecule-1 [the integrin ligand selectively expressed in the gut]. We hypothesised that this selective agent would not affect central nervous system immune surveillance. Methods: Cerebrospinal fluid from five healthy volunteers, and from 10 patients with Crohn's disease previously treated with immunosuppressants, was evaluated to assess the feasibility of the study. Subsequently, 39 patients with active Crohn's disease and previous immunosuppression were evaluated over 12 weeks of PF-00547659-induction therapy. We measured total lymphocytes, T cell subsets in cerebrospinal fluid, and circulating β7+ memory cells. Disease activity was assessed using the Harvey–Bradshaw Index. Results: Patients treated with PF-00547659 had no reduction of cerebrospinal fluid lymphocytes, T-lymphocyte subsets, or CD4:CD8 ratio, whereas circulating β7+ memory cells increased significantly. A total of 28/35 [80%] patients had a clinical response and 27/34 [79%] had disease remission. Treatment-related adverse events, none serious, were reported in 23/49 [47%] patients. Conclusions: In patients with active Crohn's disease, natalizumab therapy increases the risk for PML, and the increased risk is thought to be associated with iatrogenic leukopenia within the CNS. PML under PF-00547659 may be a lesser concern, as this agent did not reduce lymphocytes or T cell subsets in the cerebrospinal fluid.